Internal Limiting Membrane Peeling and Flap Inverting under Air in Large Idiopathic Macular Hole Surgery - Yuan Zong; Kaicheng Wu; Jian Yu; Changbo Zhou; Chunhui Jiang (Journal of Ophthalmology)
Purpose. To evaluate the efficacy of internal limiting membrane (ILM) peeling combined with modified flap inverting under air in the treatment of large idiopathic macular hole (MH). Methods. Eyes with a large idiopathic MH (minimum diameter >550 μm) were included in this study. The surgical procedure included standard 23-gauge pars plana vitrectomy (PPV), ILM peeling, complete fluid-gas exchange, and ILM flap inversion under air. The patients underwent follow-up exam including optical coherence tomography (OCT) and best-corrected visual acuity (BCVA) measurement. Results. Sixteen eyes from 16 patients were included. Mean MH diameter was 681.43 ± 112.12 μm. After a mean follow-up time of 6.25 ± 2.65 months, in all cases, the MH was closed, and the ILM flap could be seen at the inner surface of the fovea. U-shaped and V-shaped MH closure was achieved in 11 and 5 cases, respectively. The BCVA improved significantly from 1.49 ± 0.35 logMAR to 0.89 ± 0.35 logMAR (p<0.05), and visual acuity of 20/100 or better was achieved in 8 eyes. Conclusion. ILM flap inverting under air was helpful in improving the functional and anatomic outcomes of vitrectomy for large idiopathic MH.